2019
DOI: 10.1016/j.expneurol.2019.112973
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in SLC6A1 associated with Lennox-Gastaut syndrome impairs GABA transporter 1 protein trafficking and function

Abstract: Background: Mutations in SLC6A1 have been associated mainly with myoclonic atonic epilepsy (MAE) and intellectual disability. We identified a novel missense mutation in a patient with Lennox-Gastaut syndrome (LGS) characterized by severe seizures and developmental delay. Methods: Exome Sequencing was performed in an epilepsy patient cohort. The impact of the mutation was evaluated by 3H γ-aminobutyric acid (GABA) uptake, structural modeling, live cell microscopy, cell surface biotinylation and a high-through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…It has been shown that SLC6A1 variants also cause impaired protein trafficking. Characterization of a missense variant in SLC6A1 (G234S) associated with Lennox–Gastaut syndrome leads to reduced protein expression in both cell surface and total protein levels in heterologous and rat cortical neurons ( Cai et al , 2019 ). The surface protein level of the mutant is about 70% of the wild type, while the GABA uptake of the mutant GAT1 is ∼30% of the wild type.…”
Section: Towards a Model Of Slc6a1 Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that SLC6A1 variants also cause impaired protein trafficking. Characterization of a missense variant in SLC6A1 (G234S) associated with Lennox–Gastaut syndrome leads to reduced protein expression in both cell surface and total protein levels in heterologous and rat cortical neurons ( Cai et al , 2019 ). The surface protein level of the mutant is about 70% of the wild type, while the GABA uptake of the mutant GAT1 is ∼30% of the wild type.…”
Section: Towards a Model Of Slc6a1 Pathophysiologymentioning
confidence: 99%
“…The surface protein level of the mutant is about 70% of the wild type, while the GABA uptake of the mutant GAT1 is ∼30% of the wild type. This suggests the mutant GAT1 had impaired GABA uptake in addition to impaired protein trafficking ( Cai et al , 2019 ). Similarly, a recent report on SLC6A1 (P361T) associated with epilepsy and autism indicates that the mutant GAT-1 had endoplasmic reticulum retention and enhanced degradation ( Wang et al., 2020 ).…”
Section: Towards a Model Of Slc6a1 Pathophysiologymentioning
confidence: 99%
“…After reports of SLC6A1 variants in patients with myoclonic atonic epilepsy (Dikow et al, 2014;Carvill et al, 2015;Mattison et al, 2018;Cai et al, 2019;Posar and Visconti, 2019), clinical, neurophysiological, and genetic examination of a relatively large cohort of subjects (n = 34) bearing SLC6A1 mutations demonstrated that 97% of them exhibited varying degrees of intellectual disability (ID) and that 91% had been diagnosed with epilepsy (absence, myoclonic, or atonic) based on EEG patterns characterized by irregular, high, ample, generalized spikes, and wave discharges (Johannesen et al, 2018). Notably, more than 60% of these subjects had suffered from moderate or significant ID before epilepsy onset, whereas in a limited number of cases, the ID was not accompanied by epilepsy.…”
Section: Recent Studies Suggest a Less Simplistic Scenariomentioning
confidence: 99%
“…Many of the affected epilepsy genes are ion channels and transporters; thus, previous studies have been logically focused on the function of the mutant ion channels and transporters. 6,7 However, it is unclear whether alteration of the ion channel or transporter function is the whole story of the basis for the epilepsy or if other factors such as neuroinflammation, which is commonly identified in acquired epilepsy, may also play a role in the pathogenesis of genetic epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation knockin (KI) mouse models of the human mutation provide an opportunity to understand the pathophysiology of disease, due to the nature of disease starting from a very clean background instead of massive tissue injury as seen in head trauma. Many of the affected epilepsy genes are ion channels and transporters; thus, previous studies have been logically focused on the function of the mutant ion channels and transporters 6,7 . However, it is unclear whether alteration of the ion channel or transporter function is the whole story of the basis for the epilepsy or if other factors such as neuroinflammation, which is commonly identified in acquired epilepsy, may also play a role in the pathogenesis of genetic epilepsy.…”
Section: Introductionmentioning
confidence: 99%